Sobre a exogenia discursiva na profissão docente e a comunicação em Luhmann - Amaral, Joseane (Linguagens & Cidadania, 2017)
This paper aims to discuss the linguistic concept of discursive exogenous in teacher work, even as Luhmann’s impression about how to happens the communication phenomenon in society. So, we intend clarify especially how the cognitive expectations interven in educator actions, conducting some changes in this profession and also bring modifications to the system and to the social role of teacher.